Supported ionic liquids as efficient materials to remove nonsteroidal anti-inflammatory drugs from aqueous media - Almeida, Hugo F. D. (2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are largely consumed worldwide. As a result, NSAIDs were already found in a variety of environmental aqueous samples, in concentrations ranging from ng/L to µg/L. This is due to the inability of the currently used technologies in sewage treatment plants (STPs) and wastewater treatment plants (WWTPs) to completely remove such pollutants/contaminants, thus leading to serious environmental and public health concerns. This work addresses the preparation and application of materials based on silica chemically modified with ionic liquids (SILs) as alternative adsorbents to remove NSAIDs from aqueous media. Modified silica-based materials comprising the 1-methyl-3-propylimidazolium cation combined with six anions were prepared, and chemically and morphologically characterized. Adsorption kinetics, diffusion models and isotherms of sodium diclofenac – as one of the most worldwide consumed NSAIDs – were determined at 298 K. The Boyd’s film diffusion and Webber’s pore diffusion models were used to disclose the rate controlling step affecting the adsorption process. A maximum equilibrium concentration of sodium diclofenac of 0.74 mmol (0.235 g) per g of adsorbent was obtained. Several solvents were tested to remove diclofenac and to regenerate SILs, being the mixture composed of 1-butanol and water (85:15, v:v) identified as the most promising and eco-friendly. After 3 regeneration steps, the material is able to keep up to 75% of its initial adsorption efficiency. Considering the maximum values reported for sodium diclofenac in effluents from WWTPs/STPs, 1 g of the most efficient material is “ideally” able to treat ca. 50,000 L of water. These materials can thus be envisioned as efficient filters to be implemented at domestic environment in countries where the levels of pharmaceuticals are particularly high in drinking water.